PERNIKAHAN ASSILARIANG BERTINGKAT (Studi Kasus Lima Keluarga Pelaku Pernikahan Assilariang Bertingkat di Desa Balangloe Kabupaten Jeneponto) - Henri Henri; Syamsu A Kamaruddin; Idham Irwansyah Idrus; Najamuddin Najamuddin (Phinisi Integration Review, 2023)
The aims of the study areto analyze 1) the factors causing multilevel assilariang marriageof five families in Balangloe Village un Jeneponto Regency, 2) the dynamics of sanctions for perpetrators of multilevel assilariang marriageof five families in Balangloe Village in Jeneponto Regency, 3) the efforts made by five families in Balangloe Village in Jeneponto Regency in breaking the chain of multilevel assilariang marriage. The results of the study revealthat 1) there are two factors of the background of multilevel assilariang marriage, namely internal factors including parents who are less adaptive to children, hereditary habits from the family, couples love each other, and do not get the blessing of parents; while the external factors are social patterns that are less conducive due to the influence of technological progress; 2) the dynamics of sanctions for perpetrators of multilevel assilaria marriage can be viewed from two types of sanctions in terms of the customary sanctions given to assilaiang marriage actors, namely light beatings in the form of slaps; whereas, the social sanctions, namely the family will be used as a negative topic of conversation at every opportunity for gatherings in the community; and 3) there have been various efforts made to break the chain of multilevel assilaria marriage, namely by controlling the association of children, improving the quality of education, instilling an open mindset, and forming a harmonious family.Penelitian ini bertujuan 1) untuk menganalisis beberapa faktor penyebab terjadinya pernikahan assilariang bertingkat lima keluarga di Desa Balangloe Kabupaten Jeneponto, 2) untuk menganalisis dinamika sanksi pada pelaku pernikahan assilariang bertingkat lima keluarga di Desa Balangloe Kabupaten Jeneponto, 3) untuk menganalisis upaya yang di lakukan oleh lima keluarga di Desa Balangloe Kabupaten Jeneponto dalam memutus mata rantai pernikahan assilariang bertingkat. Pada hasil penelitian menunjukkan bahwa; 1) Ada dua faktor yang melatar belakangi pernikahan assilariang bertingkat yaitu faktor internal seperti orang tua yang kurang adaptif terhadap anak, kebiasaan turun temurun dari keluarga, pasangan tidak ada restu dari salah satu pihak keluarga, sedangkan faktor eksternal yaitu pola pergaulan yang kurang kondusif karena pengaruh kemajuan teknologi. 2) Dinamika sanksi bagi pelaku pernikahan assilariang bertingkat dapat ditinjau dari dua jenis sanksi, yaitu dari segi sanksi adat yang diberikan kepada para pelaku pernikahan assilariang yaitu pemukulan ringan berupa tamparan dan sanksi sosial yaitu keluarga akan di jadikan sebagai topik pembicaraan negatif dalam setiap kesempatan perkumpulan di masyarakat. 3) Ada berbagai upaya yang dilakukan dalam memutus mata rantai pernikahan assilariang bertingkat, yaitu dengan mengontrol pergaulan anak, meningkatkan kualitas pendidikan, menanamkan pola pikir terbuka dan membentuk keluarga yang harmonis.